THE IMPORTANCE OF HIGHER EDUCATION IN TRAINING OF ACADEMIC PERSONNEL - Shebashev, Viktor; Nizova, Lyudmila; Andrianov, Yuri; Furin, Alexander; Andreeva, Ekaterina (Journal of Applied Engineering Science, 2020)
The authors scrutinized a system of factors that clinch the training course of academic personnel in higher education. The authors monitored the share of researchers by age groups, science domains and activity sectors within the national project “Science”. The paper focuses on the experience of training of academic personnel at Volga State University of Technology, which is the subject of advancing and functioning of academic staff.